PENGARUH NARSISME CEO TERHADAP KUALITAS LABA DALAM LAPORAN KEUANGAN DENGAN VARIABEL KONTROL SIZE DAN EDUC - Rianty N, Martha; Rani, Sasika (Universitas Muhammadiyah Palembang, 2021)
This study was conducted to determine the effect of CEO narcissism on earnings quality by using SIZE and EDUC as control variables. The population in this study were all state-owned companies that were listed on the Indonesia Stock Exchange from 2015 to the observation period in 2018. The total population was 20. The method used was purposive sampling to determine the sample. CEO narcissism is measured by the size of the CEO's self-image in the company's annual report. Measurement of accrual earnings management is done using the Modified Jones Model. The results of the study concluded that CEO narcissism and the control variable SIZE had an effect on earnings quality. The EDUC control variable has no significant effect on the quality of earnings of BUMN companies in Indonesia.